POLA NARASI PADA ANTOLOGI CERPEN TARIAN SALJU KARABAN - Novi Diah Haryanti (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2019)
Abstract: This study aims to look at narrative patterns in the collection of short stories "Karaban Snow Dance" (TSK). From the fifteen short stories, the researchers took five main stories, namely the Karaban Snow Dance (Tarian Salju Karaban), The Fall of a Leaf (Gugurnya Sehelai Daun),  Canting Kinanti Song (Tembang Canting Kinanti), Jagoan Men Arrived (Lelaki Jagoan Tiba), and Origami Pigeon (Merpati Origami). Of the five short stories, environmental themes and honesty appear most often. The place setting depicted shows the environment that is close to the author or according to the author's origin. The main characters in the four short stories are children, only one short story Male Hero Tiban (Lelaki Jagoan Tiban/LJK) who uses adult takoh as the main character. The child leaders in LJK only appear in the past stories of the main characters. The five short stories do not show a picture of whole parents (father and mother). The warm relationship between mother and child appears clearly, in contrast to the father-child relationship that is almost negligent. The five short stories also represent how children become heroes for their family, friends, and environment.Abstrak: Penelitian ini bertujuan untuk melihat pola narasi pada kumpulan cerpen Tarian Salju Karaban (TSK). Dari limabelas cerpen yang ada, peneliti mengambil lima cerpen utama yakni “Tarian Salju Karaban”, “Gugurnya Sehelai Daun”, “Tembang Canting Kinanti”, “Lelaki Jagoan Tiba”, dan “Merpati Origami”. Kelima cerpen menampilkan tema lingkungan dan kejujuran. Latar tempat yang digambarkan memperlihatkan lingkuangan yang dekat dengan penulis atau sesuai dengan asal usul penulis. Tokoh utama dalam keempat cerpen tersebut ialah anak-anak, hanya satu cerpen “Lelaki Jagoan Tiban” (LJK) yang menggunakan takoh dewasa sebagai tokoh utama. Tokoh anak dalam LJK hanya muncul dalam cerita masa lalu tokoh utama. Kelima cerpen tersebut tidak memperlihatkan gambaran orangtua utuh (ayah dan ibu). Relasi yang hangat antara ibu dan anak muncul dengan jelas, berbeda dengan relasi bapak-anak yang nyaris alpa. Kelima  cerpen tersebut juga merepresentasikan bagaimana anak-anak menjadi pahlawan bagi keluarga, sahabat, dan lingkungannya.